Properties and testing techniques of inorganic materials. III : selected peer reviewed papers from the 8th Annual Meeting on Testing and Evaluation of Advanced Materials, July 19-21, 2017, Kunming, China - Bao, Yiwang; Jiang, Dan Yu; Gong, Jianghong (Key engineering materials, 2018)
This book comprises papers presented at the Eighth Annual Meeting on Testing and Evaluation of Advanced Materials (8th TEIM), which was held from July 19 to 21, 2017, in Kunming, China. The topics of the conference covered most aspects of analysis techniques for chemical composition and microstructures, and testing techniques of mechanical, chemical, and physical properties of advanced materials (mainly inorganic materials, including ceramics, glasses, concretes, synthesized crystals, etc.), and reflects the newest developments in these fields in China. Testing and Evaluation, Mechanical Properties, Inorganic Materials, Composites, Polymers, Ceramics, Nanomaterials, Glass, Refractories, Building Materials Materials Science.